DESARROLLO DE UN APLICATIVO MÓVIL PARA EL REPORTE DE INCIDENCIAS EN LA IE VIRGEN DE FÁTIMA N°20402- HUARAL - Casana Loyola, Juan Joel (2022)
The research carried out which bears the title of development of a software for the management of appointments of the Calderón Dental Clinic of Ica, period 2020, the clinic faces various operational problems with a greater presence in the appointment management process, which is why it is essential an IT solution that can optimize all business activities appropriately. For the purpose, it was established that, through the application of a traditional software development model and the use of the RUP methodology, which will be used for the construction of the product resulting from the research in an organized way, having as a choice of programming language PHP and as a MySQL database manager, in the same way, application of technologies such as Bootstrap, JavaScript, among others, which will allow a better integration and final functionality. KEYWORDS: Software, development, RUP, management, data, As-Is, To-Be, quantitative, experimental, descriptive, MySQL, PHP, methodology.